Invenções da cultura culinária paranaense : a festa nacional do carneiro no buraco de Campo Mourão - Paraná (1962-2014) - Martins, Bruna Morante Lacerda (2016)
Ten years after the UNESCO declaration on the ?Convention for Safeguarding Intangible Cultural Heritage? (2003) many questions stand out and seem relevant: what is the process of acknowledging an intangible cultural heritage ?know-how? like? Which elements legitimate it or which interventions are capable of turning an ?invention? into a collective heritage? In order to reflect on these aspects we sought to investigate the Carneiro no Buraco National Party and the rituals it encompasses as an ?invented tradition?, between 1962 and 2014. The delicacy is registered as a cultural heritage of Campo Mourão, Paraná. The selected period corresponds to the time when the party became official and, afterwards, when the delicacy was considered part of the city?s cultural heritage. The process of becoming a cultural heritage developed according to the public policies towards the preservation of intangible heritages which enabled the acknowledgements of several cultural practices, traditions, festivities and commensalities, such as UNESCO?s ?Convention for Safeguarding Intangible Cultural Heritage? (2003) and the ?Decreto 3.551, 04 de agosto de 2000? in Brazil. The relevance of this approach relies on the fact that the ?invention of traditions? is a common practice in Northern and Northwestern Paraná and is attached to the interests of those who saw the propagation of a traditional dish as a way to attract revenue and to foster the city?s tourist attractions. The theoretical framework of this research consists in the propositions of Nestor Canclini (2011), Paul Ricouer (2010), Michel de Certeau (1994), Eric Hobsbawm and Terence Ranger (1997), which helped us to establish the memory as a representation of what some understand as a ?practice? that should not be forgotten and as a ?know-how? pregnant with meanings that extends from the individual to the collective. In order to understand the party, we split the research in two stages: in the first one, we focused on the invention of the dish, exploring the elements of its composition and its changes in time from its origin to its standardization, and demonstrated the historical process of the transmission of knowledge among the cooks of the delicacy. In the second stage, we expounded the consolidation of the institutional powers concerning actions of festive territorialities, such as: the incorporation of a theatrical play that tells the story of the dish during the party, the ?Ritual de Acendimento? and the ?Ritual de Retirada dos Tachos?. The adopted methodological procedures consist in the analysis of the legislation, photographs and concise interviews with people involved with the party, and the historiographical works on the topic. The Carneiro no Buraco National Party, an invented tradition, aims at gathering several interests around the dish in order to forge an identity to the city dwellers, which implies its dynamic character. In fact, the acknowledgement of the ?know-how? as a cultural heritage is relevant, but it is necessary to aim for its valorization and transmission, not only for its touristic character